The Effect of the Agriculture, Tourism, and Trade Sectors on Economic Growth in Lombok Timur Regency - Hasbi Jadid Rozikin; Baiq. Ismiwati; Endang Astuti (Tinta Emas Publisher, 2024)
Economic growth is an important part of overall national development with the ultimate goal of improving people's welfare. Economic growth is one of the indicators used to see the performance of the economy both at the national and regional levels. This study aims to determine the effect of the agriculture, tourism and trade sectors on economic growth in Lombok Timur Regency. The type of research used in this study is quantitative research. The data collection method used is a case study. The data collection techniques used are documentation, literature study, and observation. The type of data used in this research is secondary data. Data is processed using the EVIEWS 10 application using the multiple linear regression method. Based on the results obtained in this study, it shows that the agricultural sector variable has a significant positive effect on economic growth, while the tourism sector and trade sector variables have a significant negative effect on economic growth. The study suggests that while the agricultural sector positively impacts economic growth in Lombok Timur Regency, there are challenges within the tourism and trade sectors that need to be addressed to fully harness their potential for development.